Detection and phylogenetic analysis of Streptobacillus moniliformis, the causative agent of rat-bite fever and Haverhill fever, in free-living greater bandicoot rats in Northeastern India - A. A. P. Milton; Aleimo G. Momin; K. Srinivas; G. Bhuvana Priya; P. N. Gandhale; D. M. Firake; Samir Das; S. Ghatak; A. Sen (Veterinary World, 2025)
Background and Aim: Streptobacillus moniliformis is the causative agent of zoonotic diseases such as rat-bite fever (RBF) and Haverhill fever (HF). While human infections are well-documented, limited studies have explored its presence in rodents in India. This study aimed to detect S. moniliformis in free-living bandicoots (Bandicota bengalensis and Bandicota indica) in Northeastern India and perform a phylogenetic analysis to assess its genetic relationship with global isolates.